PENGARUH STRATEGI PROMOSI MELALUI SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PRODUK ESQA YANG DIMEDIASI WOM MARKETING - Sastriani Ritonga; Nur Ahmad Bi Rahmani (STKIP Persada Khatulistiwa Sintang, 2022)
Purchase decisions are choices that consumers will take before buying a product or using a service. The success of the promotion strategy in marketing Esqa products using social media can have an impact on purchasing decisions. The purpose of this study was to determine the effect of promotional strategies, social media on purchasing decisions on Esqa products. This type of research is quantitative with a survey method. The data obtained by distributing questionnaires to respondents. Respondents in this study were consumers of esqa products in the city of Medan as many as 100 respondents. The method used in this study is multiple linear regression analysis method using SPSS version 26. The data analysis technique used multiple regression analysis, and descriptive analysis was used to explain the meanings contained in it. The results showed that promotion had a positive and significant effect on decisions. purchase, Social media has a positive and significant effect on purchasing decisions. Purchase decisions are able to mediate the influence of promotions on purchasing decisions. Word of Mouth can be a promotion for purchasing decisions